Psigologiese welstand en koherensiesin - Van Eeden, Chrizanne (Potchefstroom University for Christian Higher Education, 1996)
The aim of this study was to investigate the nature of psychological well-being and sense of coherence from a salutogenic perspective, and to assess the validity of the sense of coherence construct. The nature of the salutogenic approach and sense of coherence was analysed and described according to the existing literature. The nature of psychological well-being was analysed from the perspective of personology, theoretical models about aspects of psychological health and well-being and according to specific constructs, hypothesized to be related to psychological health or well-being. The role of moderator variables which could have an influence, was also investigated. In the empirical study with a group of 550 participants, psychological well-being and a sense of coherence were operationalized by means of the following measuring instruments: Personal Orientation Inventory (POI) (Shostrom, 1974), Profile of Adaptation to Life (PAL) (Elsworth, 1981a), Affecto-meter 2 (AFM) (Kammann & Flett, 1983), General Health Questionnaire (GHQ) (Goldberg & Hillier, 1979), Sense of Coherence Scale (SOC) (Antonovsky, 1987), Satisfaction with Life Scale (SWL) (Diener et al., 1985), Coping Strategy Indicator (CSI) (Amirkhan, 1990), General Selfefficacy Scale (GSe) (Tipton & Worthington, 1984), Perceived Social Support Scale (PSS) (Procidano & Heller, 1983), Attitude about Reality Scale (AAR) (Jackson & Jeffers, 1989). The Numerical Ability sub-scale of the SAT (Fouche & Verwey, 1988) was also implemented.The data was analysed for the Total Group as well as separately for the Black and White Groups, Men and Women, Young, Middle and Older Adult Groups and Married and Unmarried Groups. In the present study the results indicated relatively good reliability indices for all scales and sub-scales except for the POI and a few other sub-scales, mainly in the case of the Black Group. The results indicated significant differences between the scores of the Black and White Groups, Men and Women, Young, Middle and Older Adult Groups and Married and Unmarried Groups with regard to psychological well-being and sense of coherence. The sense of coherence construct proved to have acceptable levels of convergent and discriminant validity and seems to be a universally applicable and valid construct, across cultural, gender and age differences as was hypothesized by Antonovsky (1993). From the second order factor analysis on the data of the Total Group as well as on that of the Black and White Groups separately, a general factor of Psychological well-being emerged, on which some operationalizations of constructs hypothesized to be . indicators of psychological health and well-being loaded relatively highly. The other factors indicated that patterns of psychological well-being could be identified in which the Black and White Groups differ in certain aspects. Recommendations for further research and practical implementation of findings were made.
Proefskrif (PhD (Psigologie))--PU vir CHO, 1997.
Keywords: Salutogenic perspective; Psychological health/well-being; Sense of coherence; Self-actualization; Adaptation to life; Affect balance; Satisfaction with life; Coping; Self-efficacy; Social support